The effects of transitioning from SITA-Standard to SITA-Fast or SITA-Faster on sensitivities below the measurement floor - Chris Bradley; Alex Pham; Jithin Yohannan (AJO International)
Objective: Determine how sensitivities below the measurement floor of the Humphrey Field Analyzer change when transitioning from Swedish Interactive Thresholding Algorithm (SITA) Standard to SITA-Fast and SITA-Faster strategies. Design: Retrospective descriptive study Participants: A total of 21,468 24-2 SITA-Standard, 4872 SITA-Fast and 3468 SITA-Faster VFs from 7917 glaucoma and glaucoma suspect eyes with at least 5 VFs between 1997 and 2023 at the Wilmer Eye Institute. Methods: At each test location of the 24-2 test pattern, we measured the probability that <0 dB at a given test location on two baseline SITA-Standard VFs was M dB or higher on the first SITA-Fast or SITA-Faster post-baseline VF for different values of M > 0. Results were compared to using the same test strategy for both baseline and post-baseline VFs. Main outcome measures: Probability of <0 dB at baseline being measured as M > 0 dB or higher on the first post-baseline VF. Results: At M = 7 dB, which was approximately one standard deviation above the mean for post-baseline SITA-Standard sensitivities, average percent change from <0 dB across all test locations was 10.3 % for SITA-Standard, 15.8 % for SITA-Fast and 25.5 % for SITA-Faster. Percent change from <0 dB for all M tested (up to M = 20) was consistently higher near the macula compared to overall averages: on average 1.3 % higher for SITA-Standard, 1.5 % higher for SITA-Fast, and 6.3 % higher for SITA-Faster. Conclusions: Increased caution is advised when following the progression of <0 dB defects during a transition from SITA-Standard to SITA-Fast or SITA-Faster.